Peran Kearifan Lokal Bahuma Batahutn terhadap Kondisi Lingkungan Masyarakat Suku Dayak - Rida Respati; Muhammad Azhari; Sari Marlina (Anterior Jurnal, 2017)
The environment that continues to experience quality degradation caused by human activities in fulfilling the necessities of life such as the fulfillment of food and board clothing requires that human beings have to sacrifice what is around it for that matter. The role of government and society is very important in maintaining environmental sustainability. For example by optimizing the role of local wisdom owned by the public like Bahuma Batahutn. Bahuma Batahutn is one way of environmental management wisely, owned by the Dayak people. This type of research is a type of qualitative research using ethnographic methods and research data obtained by using data collection techniques in the form of literature review, observation, and interviews related to local wisdom.